The quality of the sporting school environment and its relationship to job satisfaction for physical education teachers in Babil Governorate - Mohammed, Ahmed Kareem; Kazar, Mazen Hadi (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research crystallized in identifying the nature of the quality of the sporting school environment and its relationship to serious creativity among teachers of physical education in the province of Babel and knowing the role of this environment on serious creativity and identifying the most important obstacles that prevent the availability of an appropriate and effective sporting school environment in order to develop and improve this environment and then upgrade to a level their professional performance in order to achieve the educational and educational process with high efficiency and effectiveness.The research problem focused on the difference in the prevailing sporting school environment in schools, as there are many schools that lack a good school environment, while some of them have a good school environment, and this difference may cause a difference in desire and the level of performance and work as a result of the different needs available to implement The lesson is in the right way, and from here the researchers saw the conduct of this study, with the aim of highlighting the role of the school sports environment and its relationship to serious creativity among physical education teachers. As the aim of the research is to return to several objectives, including building a measure of the quality of the sports school environment for physical education teachers in Babil Governorate, preparing a scale of job satisfaction for physical education teachers in Babil Province, and getting to know the reality of both (the quality of the school sport environment and job satisfaction) for teachers of physical education In Babel governorate, and to identify the statistically significant differences according to the length of service for both the quality of the sporting school environment and job satisfaction among physical education teachers in Babel governorate, and to identify the correlation between school environment quality and job satisfaction with physical education teachers in Babel governorate.The two researchers used the descriptive approach with the survey method and the associative and comparison studies. The most important conclusions reached by the researchers are that there are statistically significant differences between the teachers of physical education according to (the period of service) on the quality variable of the school sports environment and the variable of job satisfaction.